PENGEMBANGAN MINIATUR ALAT TRANSPORTASI DARAT PADA PEMBELAJARAN GEOMETRI DI KELAS IV SD - Tanti Nurwanti; Dinda Yarshal (Sekolah Tinggi Pariwisata Mataram, 2023)
This development research aims to determine the process of developing miniature media for land transportation in geometry learning that is suitable for use in elementary schools. This research is a type of research and development (Research and Development) using the ADDIE development model which consists of 5 stages, namely. Analysis (Analysis). Design (Design). Development (Development), Implementation (Implementation) and Evaluation (Evaluation). In this development the ADDIE development model is carried out only up to the 3rd stage, namely Development. The instruments used were a material expert questionnaire, a media expert questionnaire and a learning expert questionnaire to determine the feasibility of miniature land transportation media in the developed geometry learning. Based on the validation results from the material expert validator, a percentage of 80% was obtained with the